Fluorine-18: Radiochemistry and Target-Specific PET Molecular Probes Design - Wang, Yunze; Lin, Qingyu; Shi, Hongcheng; Cheng, Dengfeng (Frontiers in Chemistry, 2022)
The positron emission tomography (PET) molecular imaging technology has gained its universal value as a critical tool for assessing biological and biochemical processes in living subjects. The favorable chemical, physical and nuclear characteristics of fluorine-18 (97 % β+ decay, 109.8 min half-life, 635 keV positron energy) make it as an attractive nuclide for labeling and molecular imaging. 2-[18F]fluoro-2-deoxy-D-glucose ([18F]FDG) is the most popular PET tracer. Besides that, a significant abundant proportion of PET probes in clinical use or under development containing a fluorine or fluoroalkyl substituent group. For the reasons given above, 18F-labeled radiotracer design has become a hot topic in radiochemistry and radiopharmaceutics development. Over the past decades, we have witnessed a rapid growth in 18F-labeling methods owing to the development of new reagents and catalysts. This review aims to provide an overview of strategies in radiosynthesis of [18F]fluorine-containing moieties with nucleophilic [18F]fluorides since 2015.